Development and application of a temperature gradient detector for manned underwater robot. (20th August 2020) - Li, Dewei; Li, Ye; Ding, Zhongjun; Wang, Xiangxin; Liu, Baohua
Manned underwater robot is an important platform to carry various sensors and working tools to finish the in situ measurement and sampling in the deep sea. Due to its limited loading capacity, the device it will be carried, usually, requires to be able to dive to its working depth with a small volume and weight. According to the application requirements of deep-sea sediment temperature gradient in situ measurement observed, a detector system that can obtain data in situ is designed, which mainly includes a titanium alloy electronic cabin and a temperature probe. A comprehensive design analysis method is used to compare and analyze the ultimate static pressure, stability limit load, bending moment load, and transient temperature field on the underwater operation conditions. Optimal dimensions and filled media in the probe are decided. Finally, the pressure resistance test is finished in the lab, and scientific application is conducted on Jiaolong's 127th dive in the Northwest Indian Ocean, which successfully sampling the temperature gradient data of deep-sea sediments in the Daxi hydrothermal area. The method introduced in this article can effectively improve the safety and reliability of deep-sea structure and greatly reduce costs throughout the design cycle.